Women at the Margins : Neglect, Punishment, and Resistance. - Garner, J. Dianne (Taylor and Francis, 2013)
A compelling look at the crisis of disadvantaged women This powerful document takes a sobering look at the phenomenon of marginalized women pushed to the edges of society, holding on with the barest of hope and extraordinary bravery. Handicapped by the increasing societal inequality they face as an everyday fact of life, these women (and in many cases, their children) have been disconnected from the mainstream for reasons of age, race, gender, health, incarceration, domestic abuse, unwanted pregnancy, unemployment, and economic circumstance. They are poor in an affluent society, powerless in.